scRNA-seq reveals aging-related immune cell types and regulators in vaginal wall from elderly women with pelvic organ prolapse - Miao, Yali; Wen, Jirui; Wang, Ling; Wen, Qiao; Cheng, Juan; Zhao, Zhiwei; Wu, Jiang (Frontiers in Immunology, 2023)
In the pathology of pelvic organ prolapse (POP), little is known about the contributing role of pelvic microenvironment. Also, the age-related differences in pelvic microenvironment of POP patients is always ignored. In the present study, we investigated the age-related differences in pelvic microenvironment between Young POP patients and Old POP patients, and the novel cell types and critical regulators which contributes to the age-related differences. single-cell transcriptomic analyses were used to detect the changes in cell composition and gene expression from the pelvic microenvironment of control group (<60 years), Young POP group (<60 years) and Old POP group (>60 years). Then, immunohistochemistry and immunofluorescence were used to verify the novel cell types and critical regulators in the pelvic microenvironment. Furthermore, histopathological alteration and mechanical property alteration in POP with different ages were revealed by vaginal tissue histology and biomechanical testing. The up-regulated biological process in Old women with POP is mainly related to chronic inflammation, while the up-regulated biological process in Young women with POP is mainly related to extracellular matrix metabolism. Meantime, CSF3+ endothelial cells and FOLR2+ macrophages were found to play a central role in inducing pelvic chronic inflammation. Furthermore, the collagen fiber and mechanical property of POP patients decreased with aging. Taken together, this work provides a valuable resource for deciphering the aging-related immune cell types and the critical regulators in pelvic microenvironment. With better understanding of normal and abnormal events in this pelvic microenvironment, we provided rationales of personalized medicine for POP patients with different ages.